(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Chunskul J, Thongproh P, Simmasian W, Arkajag J, Tongpun S, Kanishthajata P, Prompalad S, Duangjai S, Duengkae P, Phochayavanich R, Chuaynkern C, Chuaynkern Y. 2021. Molecular identification and morphological description of Theloderma albopunctatum tadpoles from the Phu Khiao-Nam Nao Forest Complex, northeastern Thailand. Biodiversitas 22: 5145-5161. Presently, tadpole description of an external morphology and internal oral features of Theloderma albopunctatum (Anura, Rhacophoridae) is unknown. Therefore, this study aimed to describe tadpoles of T. albopunctatum from the Phu Khiao-Nam Nao Forest Complex in northeastern Thailand based molecular and morphological characters. Tadpole identification was based on molecular analyses. The 16S and COI sequences of the T. albopunctutatum tadpole had a genetic distance of 0% and 0.15% with the adults from Phu Luang Wildlife Sanctuary and Nam Nao National Park, respectively. Bayesian inference analyses of 16S, 16S+COI, and BDNF + SIA + RHO + TYR strongly supported the identity of tadpole and adults T. albopunctatum tadpoles are of medium size, with a black to ashy gray body that turns dark brown in preservative, they also exhibit elliptical body depressions and follow the keratodont row formula 1:2+2/1+1:2 or 1:1+1/1+1:1. T. albopunctatum tadpoles are generally similar to T. asperum.